Understanding Oba Yozo: A Sigmund Freud Theory on No Longer Human by Osamu Dazai - Fadilah, Jihan Nurul; Agus, Cecep (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study aims to explore the psychological depth of Oba Yozo, the protagonist in Osamu Dazai's No Longer Human, through the lens of Sigmund Freud’s psychoanalytic theory. Specifically, it focuses on the concepts of the id, ego, and superego to analyze how these psychological components influence Yozo's behavior, thoughts, and actions throughout the novel. The primary purpose of this research is to understand the underlying psychological dynamics that drive Yozo’s sense of alienation, self-doubt, and his inability to conform to societal expectations. The study employs a qualitative descriptive method with a content analysis approach to examine textual evidence from the novel. Key passages are identified and categorized according to Freud’s model of the psyche, allowing for an in-depth exploration of the protagonist's internal conflict. The findings reveal that Yozo’s behavior is largely driven by the id's impulsive desires and the ego's attempts to mediate between these urges and the moral constraints imposed by the superego. The analysis also demonstrates how Yozo’s inability to achieve balance between these components leads to his profound sense of despair, isolation, and eventual tragic fate. This research contributes to a deeper understanding of the psychological complexities of No Longer Human, providing a fresh perspective on the novel’s portrayal of existential struggles and the human condition. By applying Freud’s psychoanalysis, this study sheds light on the ways in which unconscious drives shape literary characters and their interactions with the world around them.